Dampak Advertising Dan Personal Selling Terhadap Volume Penjualan Telepon Selular Samsung: Studi Kasus Pada PT. Prima Nusa Abadi Surabaya - Istianik Istianik; Soedarno Sastrowidjojo (Journal of Management and Creative Business, 2025)
Marketing activities carried out by the company must be able to provide satisfaction to consumers, thus it can be said that marketing plays an important role in supporting the company's activities in increasing sales volume. Nowadays, increasingly tight competition conditions seem to close the opportunity for companies to make decisions to determine strategies to increase their selling prices, because if the selling price is increased, it does not close the opportunity for customers to move to other sellers (competitors). Meanwhile, to reduce the cost of production is also impossible if the company has carried out the production process effectively and efficiently in accordance with the established concept. So the only alternative that is still and always possible is to explore and explore the right strategy in the marketing concept. In marketing, promotional media as an alternative are considered as a savior if every company wants to increase sales turnover, because other aspects are considered to have been managed with tolerance limits that are beyond the limits of assumptions, especially if the company must be operated in Indonesia. Good promotion is a promotion that must be able to create a good and positive image in the eyes of prospective buyers (consumers), because with the image that can be formed it will have a positive impact on consumers to find out more deeply to what extent the values ​​​​are highlighted in the products offered.